Psychology in Nigeria: Reflections on the second half of the century (2015 – 2065) - Mefoh, Philip C (Practicum Psychologia, 2020)
This paper is a reflection on the post-fifty years of Psychology in Nigeria. It examined how psychology in Nigeria fared along a set of dimensions: strengths and weaknesses; contributions to the solution of problems in society; training provided, and standing in the scientific community. The evaluation revealed lots of unmet expectations. It also showed that psychology have also made significant progress in some areas, and have acquired multi-disciplinary status in the Nigerian university education. There is no other factor that points to the prospect of psychology in Nigeria than the trust that the Psychology Bill (Senate Bill, number 624) would soon become an Act of the National Assembly. The Psychology Bill, which is awaiting the President’s accent, is expected to revolutionize the practice and regulation of psychology in Nigeria when mainstreamed.